Stanozolol-Induced Changes in Fibrinolysis and Coagulation in Healthy Adults - Kluft, C; Preston, F E; Malia, R G; Bertina, R M; Wijngaards, G; Greaves, M; Verheijen, J H; Dooijewaard, G (Thrombosis and Haemostasis, 1984)
The effects of orally-administered stanozolol, 5 mg b. d. on fibrinolysis, coagulation and on various haematological and biochemical parameters have been studied in 16 healthy adults, 8 males and 8 females. Statistically significant enhancement of extrinsic (tissue-type) plasminogen activator activity was detected in all subjects studied. This was associated with significant increases in plasma plasminogen and a concomitant reduction in histidine-rich glycoprotein. There were no changes in plasma urokinase activity. Changes in the coagulation system included significant reduction in plasma fibrinogen and elevation of protein C and anti thrombin III. Changes in plasma lipids included significant reduction of HDL cholesterol associated with an increase in LDL triglycerides. No change occurred in total cholesterol. There were no major differences between the sexes, nor were there serious side effects.The effects of stanozolol on extrinsic (tissue-type) plasminogen activator activity, “free” plasminogen, protein C and antithrombin III, argue strongly in favour of its therapeutic potential.
Keywords: Stanozolol; Fibrinolysis; Coagulation